Pharmacokinetics of Supplemental Omega-3 Fatty Acids Esterified in Monoglycerides, Ethyl Esters, or Triglycerides in Adults in a Randomized Crossover Trial. Issue 5 (10th February 2021) - Chevalier, Laurie; Vachon, Annick; Plourde, Mélanie
ABSTRACT: Background: Omega-3 (n–3) fatty acid (FA) supplements increase blood concentrations of EPA and DHA. Most of the supplements on the market are esterified in triglycerides (TGs) or ethyl esters (EEs), which limits their absorption and may cause gastrointestinal side effects. Objective: The objective of this study was to compare the 24-h AUC of the plasma concentrations of EPA, DHA, and EPA+DHA when provided esterified in monoglycerides (MAGs), EEs, or TGs, (primary outcomes) and evaluate their side effects over 24 h (secondary outcome). Methods: This was a randomized, triple-blind, crossover, controlled clinical trial. Eleven women and 11 men between 18 and 50 y of age ingested, in random order, a single oral dose of ∼1.2 g of EPA and DHA esterified in MAGs, EEs, and TGs with low-fat meals provided during the 24-h follow-up. Eleven blood samples over 24 h were collected from each participant, and the plasma n–3 FAs were quantified. Friedman's paired ANOVA statistical rank test was used for the pharmacokinetic parameters and a chi-square statistical test was used for the side effects. Results: The 24-h AUC of plasma EPA was ∼2 times and ∼1 time higher after the MAG compared with the EE and TG forms of n–3 FAs, respectively ( P ≤ 0.0027). Effects of the EE and TG treatments did not differ. The 3 supplements had similar eructation, dysgeusia, abdominal discomfort, nausea, and bloating side effects. Conclusions: The plasma n–3 FA concentration in adults is greater after acute supplementation with n–3 FAs esterified in MAGs rather than in EEs or TGs, suggesting that with a lower dose of MAG n–3 FAs, the plasma n–3 FA concentrations attained are similar to those after higher doses of n–3 FAs esterified in EEs or TGs. This trial is registered at www.clinicaltrials.gov as NCT03897660.